Pengaruh Pelatihan Aku Dan Targetku Terhadap Motivasi Belajar Matematika Pada Siswa SMP “X” - Sandayanti, Vira; Nugraha, Sumedi; Rachmahana, Ratna Syi'fa (ANFUSINA: Journal of Psychology, 2018)
This study aimed to determine the effect of the training called “Me and My Target” on the motivation of learning Mathematics in 36 second grade students of "X" Middle School. The data was collected through Mathematics Learning Motivation Scale, interviews, and observations. This study used a pretest-posttest control group design (18 students as the experimental group and 18 students as the control group). This research was based on quantitative and qualitative analysis. Quantitative analysis was carried out using the Mann-Whitney test in order to determine student motivation in terms of learning Mathematics after had the training “Me and My Target”. Qualitative analysis is obtained through observation, interviews, and worksheets. The results of this study showed that there is a significant differences in student motivation to learn Mathematics between the experimental group and control group (Z = -3,216, p <0.05). Furthermore, there were also significant differences in the student motivation between the experimental group and control group within two weeks after training (Z = -3,876, p <0.05). In conclusion, the training called “Me and My Target” may increase the student motivation to learn Mathematics of second grade students of SMP "X".